Memórias e identidades indígenas na poética de Graça Graúna - Soares, Laís Cristina (2021)
This dissertation proposed to analyze the book Canto mestizo (1999), by Graça Graúna, in order to study the indigenous cultural configurations as weavings of a transcultural process experienced in the indigenous diaspora. The poetic productions of this writer, daughter of the people from Potiguar, bringthe memories and the practices of the original peoples with in a movement of strengthening the cosmogonies, the relationships with nature, the orality, and the ancestral knowledge. In this work, we presented a general panorama of indigenous writing in Brazil, and studied the relationship between the cross-cultural identity formation of Graça Graúna, evident in her appropriation of literate culture, of canonical reading, for example, and the writing of poetry that values indigenous societies against the exclusion caused by the creation of certain social stereotypes. This text is based on the theories proposed by Stuart Hall, Daniel Munduruku, Márcia Kambeba, Ailton Krenak, Pierre Nora, Ángel Rama, Janice Cristine Thiél, Antonio Candido, and Michael Pollak, among other intellectuals. Finally, it is noteworthy that Graça Graúna contributes with her literature to the indigenous identity existence in several traditional and contemporary contexts.